The Influence of Transformational Leadership and HEXACO Personality on Millennial Soldiers' Discipline in Indonesian Army (TNI AD) - Yudhiksa, I Made Maha; Darwin, Muhadjir; Kutanegara, Pande Made; Sumaryono (GoAcademica Research & Publishing, 2024)
This study examined the influence of transformational leadership style and HEXACO personality dimensions on the discipline of millennial soldiers in the Indonesian Army (TNI AD), focusing on leadership levels in Combat and Combat Support Battalions. The research utilized a mixed-method approach to explore how these variables interacted and contributed to enhancing soldier discipline. The findings indicated that both the transformational leadership style and the HEXACO personality dimensions significantly influenced soldier discipline. Furthermore, the study provided recommendations for applying an ideal leadership style that aligns with the unique cultural and generational characteristics in Indonesia. This research contributed to military leadership literature by offering new insights into human resource management within a military context, particularly in addressing the challenges posed by the millennial generation.